Perbaikan Postur Kerja Pegawai Lepas Perusahaan Provider Menggunakan Metode RULA - Moh Ainul Fais; Ryan Adi Pratama; Dedy Kunhadi; Bambang Sutejo; Silvana Mohamad; LM Fandy Prayogo (Jurnal Industri dan Inovasi (INVASI), 2024)
The modern era has made freelance workers a trend, freelance employees work individually from their workplace. Freelance employees provide the freedom to choose the work they want without being tied to a contract, but in practice, freelance workers are very unfulfilled, such as in the health sector and field facilities. PT. X, which is a well-known provider company in Indonesia, has problems with employees who often experience complaints such as body aches, sprains and minor injuries after work. Improving work posture is very necessary to help freelance employees feel comfortable working, so it is necessary to analyze work posture using the Rapid Upper Limb Assessment (RULA) method. The research results show that action level 4 is obtained which requires the company to immediately carry out inspections and changes (right now). The proposed improvement in this research is that there is a need to improve work methods or systems (SOP) when carrying out the cable planting fireplace process and provide complete work facilities.